Miscellaneous notes on nomenclature and taxonomy of some Old World names in tribe Paniceae (Panicoideae, Poaceae) - Crespo, Manuel B.; Alonso, María Ángeles; Martínez-Azorín, Mario; Sáez, Llorenç (Phytotaxa, 2020)
Nomenclatural types of eleven names of Paniceae described from the Old World are indicated and discussed. This includes designation of ten new types (i.e. four lectotypes, one second-step lectotype, three epitypes and two neotypes) for names currently accepted at different ranks in Cenchrus, Digitaria, Echinochloa, Oplismenus and Setaria. Furthermore, seven new combinations of infrageneric groups are also validated in Cenchrus (namely C. sect. Beckeropsis, C. sect. Brevivalvula, C. sect. Dactylophora, C. sect. Gymnotrix, C. sect. Kikuyuochloa, C. sect. Penicillaria, and C. sect. Pleurostigma) to accommodate the representatives of that genus occurring in the Iberian Peninsula and the Old World.